Lithium ion battery negative electrode slurry and application thereof

By improving the formula of the negative electrode slurry of lithium-ion batteries, the cohesion and peeling force of the electrode sheet are improved, and the cycle performance and thickness expansion rate of the battery are solved.

CN119695156APending Publication Date: 2025-03-25惠州赣锋锂电科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411878089.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The expansion of the negative electrode of lithium-ion batteries too thick leads to poor circulation performance. The prior art mainly solves the problem by improving the positive electrode material, while ignoring the influence of the negative electrode formula and preparation method.

Method used

A lithium-ion battery negative electrode slurry is provided, which consists of an anode active substance, a dispersant, a binder, an additive and water, and has a solid content of 40 to 56%. By improving the slurry formula, the cohesion and peeling force of the electrode sheet are enhanced, and the expansion of the cell cycle thickness is reduced.

Benefits of technology

By improving the negative electrode slurry formula, the peeling force and cohesion of the negative electrode sheet are significantly improved, the cell cycle thickness expansion is reduced, and the circulation performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695156A_ABST
    Figure CN119695156A_ABST
Patent Text Reader

Abstract

The invention provides lithium ion battery negative electrode slurry and application thereof, and belongs to the technical field of lithium ion batteries. In the formula of the negative electrode slurry, the negative electrode active material, the dispersing agent, the binder and the additive are mutually crosslinked to form a tight combination body, so that binder molecules are limited to move in the direction away from a current collector in the baking process, the diffusion path of the binder molecules is reduced, and the adhesive force between the active material and each component and the adhesive force of a pole piece are increased; the negative electrode expansion rate is effectively reduced and the cycle performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode slurry for lithium ion batteries and applications thereof. Background Art

[0002] After high-temperature storage and circulation, soft-pack lithium-ion batteries are prone to swelling, with a thickness increase of 6% to 20%, of which the positive electrode expansion rate is only 4% and the negative electrode expansion rate is more than 20%. For lithium-ion batteries, affected by the nature of the negative electrode, the negative electrode graphite forms LiCx (LiC24, LiC12 and LiC6, etc.) when lithium is inserted, and the lattice spacing changes, resulting in the formation of microscopic internal stress, causing the negative electrode to expand. Studies have shown that the expansion of the graphite negative electrode is mainly caused by the irreversible expansion after lithium insertion. This part of the expansion is mainly related to the particle size, binder and pole piece structure. The expansion of the negative electrode causes the coil core to deform, forming a cavity between the electrode and the diaphragm, forming microcracks in the negative electrode particles, and the solid electrolyte interface (SEI) film to rupture and reorganize, consuming electrolyte, making the cycle performance worse, and the cycle expansion is too thick, which cannot meet market demand.

[0003] Currently, there are many studies on battery cycle performance, but most of them improve battery cycle performance by using electrolyte additives to improve positive electrode materials, while ignoring the effects of negative electrode formulation and preparation methods on cycle performance and expansion. Summary of the invention

[0004] The purpose of the present invention is to provide a lithium ion battery negative electrode slurry and its application, which is of great significance for solving the technical problem in the prior art that the negative electrode of the lithium ion battery expands too thickly, resulting in poor cycle performance.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a negative electrode slurry for a lithium ion battery, which is composed of the following components in parts by mass: 96.0 to 98.0 parts of a negative electrode active material, 0.5 to 1.2 parts of a dispersant, 0.8 to 1.8 parts of a binder, 0.2 to 0.6 parts of an additive, and 75 to 155 parts of water;

[0007] The additives include one or more of a highly flexible linear high molecular polymer emulsion, an itaconate ester compound and an unsaturated resin;

[0008] The solid content of the lithium ion battery negative electrode slurry is 40-56%.

[0009] Furthermore, the negative electrode active material includes graphite and / or silicon.

[0010] Furthermore, the dispersant includes sodium carboxymethyl cellulose or lithium carboxymethyl cellulose.

[0011] Furthermore, the binder includes styrene-butadiene emulsion and / or styrene-acrylic emulsion.

[0012] Furthermore, the high-flexibility linear high-molecular polymer emulsion is polymer emulsion A or polymer emulsion B.

[0013] Furthermore, the polymer emulsion A is obtained by dispersing polyacrylic acid and / or polymethyl methacrylate in N,N-dimethylformamide.

[0014] Furthermore, the polymer emulsion B is obtained by polymerizing polyvinyl alcohol and acrylic acid monomers.

[0015] Further, the itaconate ester compound includes monobutyl itaconate and / or dibutyl itaconate;

[0016] The unsaturated resin includes linear phenolic resin and / or bisphenol epoxy resin.

[0017] Furthermore, the viscosity of the negative electrode slurry of the lithium ion battery is 3000-6000 mPa·s.

[0018] The present invention provides an application of the above-mentioned lithium ion battery negative electrode slurry in a lithium ion battery.

[0019] Beneficial effects of the present invention:

[0020] 1. The present invention improves the negative electrode slurry formula, thereby increasing the cohesion and peeling force of the electrode sheet and reducing the thickness expansion of the battery cell during cycling;

[0021] 2. The negative electrode slurry formula of the present invention can improve the quality of negative electrode coating. During the coating process, the negative electrode active material, dispersant, binder and additive components are cross-linked to form a tightly bound body, which limits the movement of binder molecules away from the current collector during the baking process, reduces the diffusion path of binder molecules, and increases the adhesion between the active material and each component and the electrode sheet adhesion;

[0022] 3. The negative electrode slurry formula adopts methods including grafting, enhancing mechanical interlocking, improving interface bonding, introducing elasticity, self-healing and electrical / ionic conductivity, topological crosslinking, etc. to modify the additives to form a linear long-chain structure with a large number of carboxyl lines, which can form ester bonds and hydrogen bond structures with the hydroxyl groups on the surface of active material particles or conductive agent particles, thereby improving the wettability and dispersibility of the polymer, improving adhesion, and improving the flexibility of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a characterization diagram of the peeling force of the negative electrode sheet of the lithium ion battery prepared in Example 1, wherein the ordinate is the peeling force and the abscissa is the peeling length;

[0024] Figure 2 This is a characterization diagram of the cohesive force of the negative electrode sheet of the lithium ion battery prepared in Example 1, wherein the ordinate is the cohesive force and the abscissa is the peeling length;

[0025] Figure 3 This is a characterization diagram of the peeling force of the negative electrode sheet of the lithium ion battery prepared in Comparative Example 1, where the ordinate is the peeling force and the abscissa is the peeling length;

[0026] Figure 4 This is a characterization diagram of the cohesive force of the negative electrode sheet of the lithium ion battery prepared in Comparative Example 1, wherein the ordinate is the cohesive force and the abscissa is the peeling length;

[0027] exist Figures 1 to 4 In each figure, there are three broken lines, representing three parallel samples;

[0028] Figure 5 The normal temperature cycle capacity retention rate diagram of the lithium ion battery prepared in Example 1 and Comparative Example 1 respectively;

[0029] Figure 6 The thickness expansion rate diagram of the lithium ion batteries prepared in Example 1 and Comparative Example 1 at room temperature;

[0030] Figure 7 The 45°C high temperature cycle capacity retention diagram of the lithium ion batteries prepared in Example 1 and Comparative Example 1 respectively;

[0031] Figure 8 The graphs are thickness expansion ratios of the lithium-ion batteries prepared in Example 1 and Comparative Example 1 respectively under high temperature conditions of 45°C. DETAILED DESCRIPTION

[0032] The present invention provides a negative electrode slurry for a lithium ion battery, which is composed of the following components in parts by mass: 96.0 to 98.0 parts of a negative electrode active material, 0.5 to 1.2 parts of a dispersant, 0.8 to 1.8 parts of a binder, 0.2 to 0.6 parts of an additive, and 75 to 155 parts of water;

[0033] The additives include one or more of a highly flexible linear high molecular polymer emulsion, an itaconate ester compound and an unsaturated resin;

[0034] The solid content of the lithium ion battery negative electrode slurry is 40-56%.

[0035] In the present invention, the content of the negative electrode active material is preferably 97 parts by mass.

[0036] In the present invention, the content of the dispersant is preferably 0.7 to 1.0 part by mass, and more preferably 0.9 part by mass.

[0037] In the present invention, the content of the binder is preferably 0.9 to 1.5 parts by mass, and more preferably 1.3 parts by mass.

[0038] In the present invention, the content of the additive is preferably 0.3 to 0.5 parts by mass, and more preferably 0.4 parts by mass.

[0039] In the present invention, the water content is preferably 80 to 130 parts by mass, and more preferably 100 parts by mass.

[0040] In the present invention, the additive is preferably one of a high-flexibility linear high-molecular polymer emulsion, an itaconate compound and an unsaturated resin, and is further preferably a high-flexibility linear high-molecular polymer emulsion.

[0041] In the present invention, the solid content of the lithium ion battery negative electrode slurry is preferably 45-50%, and more preferably 48%.

[0042] In the present invention, the negative electrode active material includes graphite and / or silicon, preferably graphite.

[0043] In the present invention, the dispersant includes sodium carboxymethyl cellulose or lithium carboxymethyl cellulose, preferably sodium carboxymethyl cellulose.

[0044] In the present invention, the binder comprises styrene-butadiene emulsion and / or styrene-acrylic emulsion, preferably styrene-butadiene emulsion or styrene-acrylic emulsion, and more preferably styrene-butadiene emulsion.

[0045] In the present invention, the high-flexibility linear high-molecular polymer emulsion is polymer emulsion A or polymer emulsion B, preferably polymer emulsion A.

[0046] In the present invention, the polymer emulsion A is preferably obtained by dispersing polyacrylic acid and / or polymethyl methacrylate in N,N-dimethylformamide.

[0047] In the present invention, the polymer emulsion B is preferably obtained by polymerizing polyvinyl alcohol and acrylic acid monomers.

[0048] In the present invention, the itaconate ester compound includes monobutyl itaconate and / or dibutyl itaconate, preferably monobutyl itaconate or dibutyl itaconate, and more preferably monobutyl itaconate;

[0049] The unsaturated resin includes linear phenolic resin and / or bisphenol epoxy resin, preferably linear phenolic resin or bisphenol epoxy resin, and more preferably linear phenolic resin.

[0050] In the present invention, the viscosity of the negative electrode slurry of the lithium ion battery is 3000-6000 mPa·s, preferably 4000-5000 mPa·s, and more preferably 4500 mPa·s.

[0051] The present invention provides an application of the above-mentioned lithium ion battery negative electrode slurry in a lithium ion battery.

[0052] In the present invention, the application of the lithium ion battery negative electrode slurry in the lithium ion battery comprises the following steps: slurry coating, pole piece baking, sheet making, rolling, stripping, winding, top and side sealing, baking, liquid injection, sealing, formation, secondary sealing, and capacity division to form a soft-pack lithium ion battery.

[0053] In the present invention, the negative electrode slurry of the lithium-ion battery forms a three-dimensional network structure on the pole piece, which greatly improves the bonding force between particles in the pole piece and between particles and the current collector.

[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0055] Example 1

[0056] Dispersing polyacrylic acid and polymethyl methacrylate in N,N-dimethylformamide to obtain a highly flexible linear polymer emulsion with a chemical formula of [C3H4O2]n, and mixing the emulsion with twice the mass of deionized water to obtain an additive;

[0057] By weight, 96.8 parts of graphite, 1.2 parts of sodium carboxymethyl cellulose, 0.6 parts of additives and an appropriate amount of water were mixed, and 1.4 parts of styrene-butadiene emulsion and the remaining water were added thereto in sequence to obtain a lithium ion battery negative electrode slurry having a viscosity of 4500 mPa.s and a solid content of 48%;

[0058] The obtained negative electrode slurry is coated on the electrode sheet, and then a soft-pack lithium-ion battery is formed after baking, sheeting, rolling, slitting, winding, top and side sealing, baking, liquid injection, sealing, formation, secondary sealing and capacity division.

[0059] Example 2

[0060] Different from Example 1, in this example, the mass fraction of the additive is 0.2 parts, the mass fraction of sodium carboxymethyl cellulose is 1.2 parts, and the mass fraction of styrene-butadiene emulsion is 1.8 parts.

[0061] Example 3

[0062] Different from Example 1, in this example, the mass fraction of the additive is 0.4 parts, the mass fraction of sodium carboxymethyl cellulose is 1.2 parts, and the mass fraction of styrene-butadiene emulsion is 1.6 parts.

[0063] Example 4

[0064] Dispersing polyacrylic acid and polymethyl methacrylate in N,N-dimethylformamide to obtain a highly flexible linear polymer emulsion with a chemical formula of [C3H4O2]n, and mixing the emulsion with twice the mass of deionized water to obtain an additive;

[0065] By weight, 97.5 parts of graphite, 0.8 parts of lithium carboxymethyl cellulose, 0.5 parts of an additive and an appropriate amount of water are mixed, and then 1.2 parts of a styrene acrylic emulsion and the remaining water are added thereto in sequence to obtain a lithium ion battery negative electrode slurry having a viscosity of 3000 mPa.s and a solid content of 40%;

[0066] The obtained negative electrode slurry is coated on the electrode sheet, and then a soft-pack lithium-ion battery is formed after baking, sheeting, rolling, slitting, winding, top and side sealing, baking, liquid injection, sealing, formation, secondary sealing and capacity division.

[0067] Example 5

[0068] Dispersing polyacrylic acid and polymethyl methacrylate in N,N-dimethylformamide to obtain a highly flexible linear polymer emulsion with a chemical formula of [C3H4O2]n, and mixing the emulsion with twice the mass of deionized water to obtain an additive;

[0069] By weight, 98 parts of graphite, 1.2 parts of lithium carboxymethyl cellulose, 0.2 parts of an additive and an appropriate amount of water are mixed, and then 1 part of a styrene acrylic emulsion and the remaining water are added thereto in sequence to obtain a lithium ion battery negative electrode slurry having a viscosity of 6000 mPa.s and a solid content of 56%;

[0070] The obtained negative electrode slurry is coated on the electrode sheet, and then a soft-pack lithium-ion battery is formed after baking, sheeting, rolling, slitting, winding, top and side sealing, baking, liquid injection, sealing, formation, secondary sealing and capacity division.

[0071] Comparative Example 1

[0072] Different from Example 1, in this comparative example, the negative electrode slurry does not contain any additive.

[0073] It can be seen from the above embodiments that the present invention provides a lithium ion battery negative electrode slurry and application thereof. Figure 1 This is a characterization diagram of the peeling force of the negative electrode sheet of the lithium ion battery prepared in Example 1. Figure 2 This is a characterization diagram of the cohesive force of the negative electrode sheet of the lithium-ion battery prepared in Example 1. Figure 3 This is a characterization diagram of the peeling force of the negative electrode sheet of the lithium ion battery prepared in Comparative Example 1. Figure 4 This is a characterization diagram of the cohesive force of the negative electrode sheet of the lithium-ion battery prepared in Comparative Example 1. Figures 1 to 4It can be seen that after adding additives to the negative electrode slurry, the peeling force and cohesive force of the negative electrode sheet are significantly improved.

[0074] Figure 5 The graphs of the cycle capacity retention rates of the lithium ion batteries prepared in Example 1 and Comparative Example 1 at room temperature are shown in FIG. Figure 6 The thickness expansion ratio diagrams of the lithium ion batteries prepared in Example 1 and Comparative Example 1 at room temperature are shown in FIG. Figure 7 The graphs are the cycle capacity retention rates of the lithium-ion batteries prepared in Example 1 and Comparative Example 1 at a high temperature of 45°C. Figure 8 The thickness expansion ratio diagrams of the lithium-ion batteries prepared in Example 1 and Comparative Example 1 at a high temperature of 45°C are shown. Figures 5 to 8 It can be seen that the capacity retention rate of the implementation group after 1000 cycles at room temperature is >80%, and the thickness expansion rate is <8%, while the capacity retention rate of the comparison group after 750 cycles is >80%, and the thickness expansion rate is >8%; the capacity retention rate of the implementation group after 500 cycles at high temperature of 45°C is >70%, and the thickness expansion rate is <6%, while the capacity retention rate of the comparison group after 500 cycles is >70%, and the thickness expansion rate is >8%. The capacity retention rate of the implementation group is significantly improved, and the thickness expansion rate is significantly reduced. It can be seen that the lithium ion battery negative electrode slurry of the present invention and its application solve the technical problem in the prior art that the negative electrode of the lithium ion battery expands too thick, resulting in poor cycle performance.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A negative electrode slurry for a lithium ion battery, characterized in that: The invention is composed of the following components in parts by weight: 96.0 to 98.0 parts of negative electrode active material, 0.5 to 1.2 parts of dispersant, 0.8 to 1.8 parts of binder, 0.2 to 0.6 parts of additive, and 75 to 155 parts of water; The additives include one or more of a highly flexible linear high molecular polymer emulsion, an itaconate ester compound and an unsaturated resin; The solid content of the lithium ion battery negative electrode slurry is 40-56%.

2. A lithium ion battery negative electrode slurry according to claim 1, characterized in that: The negative electrode active material includes graphite and / or silicon.

3. A negative electrode slurry for lithium ion batteries according to claim 1 or 2, characterized in that: The dispersant includes sodium carboxymethyl cellulose or lithium carboxymethyl cellulose.

4. The negative electrode slurry for lithium-ion batteries according to claim 3, characterized in that: The binder includes styrene-butadiene emulsion and / or styrene-acrylic emulsion.

5. A negative electrode slurry for lithium-ion batteries according to claim 1, 2 or 4, characterized in that: The high-flexibility linear high-molecular polymer emulsion is polymer emulsion A or polymer emulsion B.

6. A negative electrode slurry for lithium-ion batteries according to claim 5, characterized in that: The polymer emulsion A is obtained by dispersing polyacrylic acid and / or polymethyl methacrylate in N,N-dimethylformamide.

7. The negative electrode slurry for lithium-ion batteries according to claim 5, characterized in that: The polymer emulsion B is obtained by polymerizing polyvinyl alcohol and acrylic acid monomers.

8. The negative electrode slurry for lithium-ion batteries according to claim 1, characterized in that: The itaconate ester compound includes monobutyl itaconate and / or dibutyl itaconate; The unsaturated resin includes linear phenolic resin and / or bisphenol epoxy resin.

9. The negative electrode slurry for lithium-ion batteries according to claim 1, characterized in that: The viscosity of the negative electrode slurry of the lithium ion battery is 3000-6000 mPa·s.

10. Use of the negative electrode slurry for lithium ion batteries according to any one of claims 1 to 9 in lithium ion batteries.